2019
DOI: 10.1002/jcp.29276
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR‐183 represses neuropathic pain through inhibiton of MAP3K4 in CCI rat models

Abstract: Many studies have verified that microRNAs contribute a lot to neuropathic pain progression. Furthermore, nerve‐related inflammatory cytokines play vital roles in neuropathic pain progression. miR‐183 has been identified to have a common relationship with multiple pathological diseases. However, the potential effects of miR‐183 in the process of neuropathic pain remain undetermined. Therefore, we performed the current study with the purpose of finding the functions of miR‐183 in neuropathic pain progression usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…23 MAP3K4 also regulates the stem cell epithelial-to-mesenchymal transition (EMT), [24][25][26] cell migration, 27,28 and several inflammatory mediators including IL-6, IL-1β, and COX2. 29 Long non-coding RNAs (lncRNAs) have emerged as a class of regulatory molecules with highly diverse structures and functions in both physiological and pathological contexts. [30][31][32][33] Genome-wide transcriptome analyses have identified thousands of lncRNAs throughout the human genome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 MAP3K4 also regulates the stem cell epithelial-to-mesenchymal transition (EMT), [24][25][26] cell migration, 27,28 and several inflammatory mediators including IL-6, IL-1β, and COX2. 29 Long non-coding RNAs (lncRNAs) have emerged as a class of regulatory molecules with highly diverse structures and functions in both physiological and pathological contexts. [30][31][32][33] Genome-wide transcriptome analyses have identified thousands of lncRNAs throughout the human genome.…”
Section: Introductionmentioning
confidence: 99%
“…Chi et al reported that MAP3K4 is selective for the p38 pathway in MAP3K4 knockout mice 23 . MAP3K4 also regulates the stem cell epithelial‐to‐mesenchymal transition (EMT), 24‐26 cell migration, 27,28 and several inflammatory mediators including IL‐6, IL‐1β, and COX2 29 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, miRNAs have been reported to be abnormally expressed in the nervous system and exert essential effects to modulate neuropathic pain. For example, miR-183 overexpression inhibits neuropathic pain by targeting MAP3K4 in CCI rat models (Huang and Wang 2019 ). MiR-101 alleviates neuropathic pain in CCI rat models by downregulating mTOR expression (Xie et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-183 modulates the expression of MAP3K4, which in turn leads to the downregulation of inflammatory factors, and cyclooxygenase-2 (COX-2) which slows NP progression. In summary, the study stated that miR-183 was a part of the negative regulatory effector group, which could alleviate NP by targeting MAP3K4 ( Huang and Wang, 2020 ). MiR-21 can interact with toll-like receptor 8 (TLR8) in lysosome as an endogenous ligand, inducing extracellularly regulated protein kinase (ERK) activation and production of inflammatory mediators.…”
Section: Micrornas In Neuropathic Painmentioning
confidence: 99%